The Death and the (Eternal) Return of Nietzsche’s Zarathustra - Kruszelnicki, Michał (Hybris, 2018)
The paper argues that F. Nietzsche’s magnum opus Thus Spoke Zarathustra can be looked upon as a narrative about the protagonist’s maturation to understand, articulate and accept the thought of the eternal return which is tantamount to accepting the prospect of his own imminent death and the enigma of afterlife. I seek to prove that Zarathustra purposely defers systematic and coherent explanation of his deepest thought, as well as he dismisses its interpretations proposed by his animals, disciples, and by his main enemy – the dwarf. The thought of the eternal return can only be revealed, enacted. For this purpose, Zarathustra must actually die and return and by so doing bestow on the next generations the gift of his secret intuition. It can be argued convincingly that the last two chapters of part IV of Thus Spoke Zarathustra are conceived as a powerful performative reenactment of the thought of the eternal return as a selective force. The force, however, which does not bring a different (resp. “better”, “stronger”…) existence, as Gilles Deleuze would want it, but the very same, identical life.